The reform of solid waste management in Cairo: - El Mahdy, Hoda (AUC Knowledge Fountain, 2016)

(untitled)
Most criticism about Cairo’s dysfunctional solid waste management system has been directed towards the multinational companies managing it since 2002. This study explores the reason for this dysfunction and accordingly devises operational reform recommendations. The study relies on qualitative primary data obtained from interviewing representatives of the Egyptian government, private sector partners, workers, civil society organizations, investors and consultants during 2014 and 2015. The study also relies on the review of secondary data about different international models, particularly Brazil, which was taken as a case study for comparative analysis. The data collected shows that the current management system is ineffective due to the Egyptian government’s insufficient financial and administrative planning prior to contracting with multinational companies. Additionally, systemic problems at Cairo’s local administration level has led to a continued state of a hindrance to reform efforts. Cairo’s officials have already identified some relevant reform interventions to introduce. These include substituting the multinational companies with the national companies formed by traditional waste workers of Cairo, introducing financial and administrative reforms, encouraging recycling through applying waste segregation at source, and supporting composting and waste-to-energy technology. Success of these reform plans, however, is dependent on the national solid waste management authority’s autonomy, ability to devise and implement a national policy plan that takes different stakeholder interests into account and the capacity of waste workers to organize under legal entities.